Legislating novel psychoactive substances: lessons from 15 years of UK mortality data (2007-2022) - Rock, Kirsten L.; Treble, Ric; Copeland, Caroline S. (Frontiers in Pharmacology, 2026)
BackgroundNovel Psychoactive Substances (NPS) emerged in the early 2000s as chemically designed alternatives to circumvent laws which internationally control drugs. There is limited evidence that NPS are produced in the UK, whereas China has long been recognised as a primary source of NPS. This study aimed to evaluate the relative impact of UK, Chinese, and UN legislative controls on the availability of NPS in the UK, as evidenced by post-mortem detections of NPS in deaths.MethodsDeaths reported to the National Programme on Substance Use Mortality (NPSUM) which occurred 2007–2022 were extracted for analysis. Drugs from the three major substance classes–opioids, stimulants and cannabinoids–which were detected in these deaths were categorised according to their control status as either classical substances (i.e., those under international control prior to 2007), NPS controlled in China, or other NPS.FindingsAcross all three drug classes, detections of classical substances dominated throughout the study period. Detections of NPS opioids–primarily fentanyl analogues–peaked in 2017, NPS stimulants–notably cathinones–in 2015, and synthetic cannabinoid receptor agonists in 2018 and 2021. Whilst UK legislative controls (the Misuse of Drugs Act 1971, Temporary Class Drug Orders, the Psychoactive Substances Act 2016) were generally implemented first, reductions in NPS detections were more closely associated with the introduction of Chinese legislations - in particular the 2021 Chinese generic ban on synthetic cannabinoids which resulted in an almost complete disappearance of these compounds in UK deaths in 2022.ConclusionThe findings of this study indicate that the most effective way to reduce NPS availability in the UK is via legislation in producer countries, as evidenced by substantial declines in their detections in deaths following their control in China. This reliance on international controls places the UK in a vulnerable position, as its domestic drug landscape is being shaped largely by the pace and scope of independent international legislations. To achieve and maximise effectiveness, UK drug policy needs to integrate harm reduction measures alongside the introduction of legislative controls, whilst also encouraging international efforts to bring in global control of problem materials.